Introducing E-Commerce to Achieve a Productive and Entrepreneurial Village - Fitri Amilia; Nurkamilah Nurkamilah; Gitta Rowindi (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The present community service is carried out to provide business development opportunities in the village of Karangduren, Balung, Jember. There are relatively many entrepreneurs in the fields of fish breeding, breeding flowers and various plants, making food and various snacks, and handicrafts registered in Karangduren. In collaboration with the Muhammadiyah University of Jember, this activity was initiated with the theme of introducing e-commerce to the enterpreneurs in order to help Karangduren become an entrepreneurial village. The implementation of this service involves 2 lecturers and 2 students of the Faculty of Teacher Training and Education. The activity was carried out at the Karangduren Village Hall, participated by 17 business owners. Because this activity was carried out during the pandemic, there were restrictions on the number of participants and compliance with the Covid 19 health protocols. The team presented general overview of e-commerce and marketplace in a lecture format as well as distributed a module to every attending participant. After about an hour of lecture and a question and answer session, the team helped the participants to build their virtual business account using WhatsApp (WA) business. Some participants practiced creating a WA business account and opening a shop on the market place. In addition, in the practice of creating a WA business account, the participants also created a catalog containing their product offerings. In the post-activity, the team interviewed some participants, and they appreciated the team for this activity. Through this, they are expecting their business to be known more widely thus obtain more income. New knowledge and skills in managing this virtual business will continue to be improved so that people can live independently and form new thoughts towards productive and entrepreneurial villages in the future.